Fontes e doses de N, P, K e métodos de enxertia na produção de mudas de umbuzeiro (Spondias tuberosa Arr. Cam.) - Andrade, Miguel Wanderley de (Universidade Federal Rural do Semi-Árido, 2010)
The objective of this study was to determine the effect of sources and doses of NPK and to evaluate the propagation by grafting for the production of vigorous seedlings of umbu tree (Spondias tuberosa Arr Cam). The experiments were conducted in greenhouse in Sousa-PB. We adopted the randomized block design in 2 x 5 factorial scheme with four replications for all experiments with macronutrients. First, we tested urea and ammonium sulfate at five rates: 0, 350, 700, 1400 e 2800 mg.dm-3 substrate. Were subsequently evaluated two sources of potassium fertilizer (potassium chloride and potassium sulfate) in five doses of K20: 0, 1800, 3600, 5400 e 7200 mg.dm-3. In the last test, we tested phosphate fertilizer (MAP) at doses of P2O5: 0; 450; 900; 1350 e 1800 mg.dm-3 substrate, and superphosphate doses of P2O5: 0; 450; 900; 1350 e 1800 mg.dm-3 substrate. In the experiment regarding the methods of grafting, we used a randomized block design with four replications in a split plot in time, standing in five installments grafting (budding, cleft graft, stub graft, whip graft and tongue graft) and the plots, the four assessment periods (intervals of 15 days for sixty days), each experimental unit consisted of 15 plants. The increase in nitrogen and potassium applied negatively influenced the survival of seedlings, shoot length, stem diameter and fresh weight of root. The response to phosphorus fertilization showed to shoot dry matter and xylopodium production in dose 1350 and 450 mg.dm-3 P2O5, respectively. The grafting methods cleft graft and whip graft had the highest number of shoots (58,5%) in plants of umbu tree
Primary macronutrients (NPK) and grafting in the production of seedlings of Spondias tuberosa Arr. Cam.)
Keywords: Fruit culture; vegetative propagation; macronutrients; umbu tree; Fruticultura; macronutrientes; propagação vegetativa; umbuzeiro; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA